GAMBARAN NILAI PASAR TERHADAP RETURN SAHAM PADA PERUSAHAAN SUBSEKTOR ADVERTISING PRINTING MEDIA YANG TERDAFTAR DI BEI PERIODE 2010-2016 - Destiana, Prisila; Surachim, Ahim; Sulastri, Sulastri (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this research are to descript of market value, the descript of stock return, while the purpose of this study is to determine the description of perception market value to return saham in subsector advertising printing media.Design / methodology / approach - Method in this research used descriptive and verification methods. Data that used are secondary data of each subsector advertising printing media with analysis technique using multiple linear regression. Sampling in this research use purposive sampling.Findings - The results of this research indicate that market value measured by Price Earning Ratio (PER) and Price to Book Value (PBV) has significance to return saham. The result showed that the market value Â has a positive Â effect return saham.Originality -The difference of this research with previous research is on research object, population and research sample, research period, measuring instrument and research result, as well as foreign theory and journal source and foreign book and research result.